Positive and Negative Effects of Non-Formal Adult Learning on Social Relationships Based on the Results of a Research (Training and Practice : Journal of Educational Sciences, 2015)
In the first part of her article Kispálné Horváth Mária provides an overview of professional literature about the effects of adult learning on social relationships. In the second part she presents the results of a research carried out in 2013 which are related to the positive and negative effects of non-formal adult learning on social relationships. The 350 respondents are learning in various types of trainings including, for example, recreational clubs, cultural and artistic courses, sports clubs, religious trainings and life skills courses. Regarding the possible positive effects the author demonstrates the looser and tighter ways of broadening social relationships as well as family background which can support learning. Finally, as for the negative effects, the results relating to conflicts with other adult learners and family members are shown.